The Importance of Technology-Based Learning Design to Increase Student Involvement - Hafizh, Muhammad; M, Amril Huda; Dafrizal, Dafrizal; Edni, Alisya Putri (Ahlussunnah: Journal of Islamic Education, 2024)
This research examines the use of animation as a technology-based learning medium to increase student learning motivation. In the rapid development of information and communication technology, education requires innovative transformations in learning methods. Animation has been recognized as an effective tool for enriching students' learning experiences through clear and interactive visual representations. This research aims to analyze literature related to the use of animation as a learning medium, explore the advantages and challenges of its use, and convey the contribution of this research to the development of innovative learning practices. The method used in this research is a literature study, where data is obtained through analysis of theoretical sources and related research. The results of the literature study analysis show that animation has great potential to increase student learning motivation, involvement, creativity, and personalized learning. However, educators and researchers need to pay attention to good animation design and the role of educators in facilitating the effective use of animation. This research contributes to the development of innovative learning practices and enriches understanding of the use of animation as an effective learning medium in increasing student learning motivation.